PERANCANGAN SISTEM DIGESTER BIOGAS PADA SKALA RUMAH TANGGA - Mauludi, Mohammad Zidan; Dhofir, Moch.; Yudaningtyas, Erni (Jurnal Mahasiswa TEUB, 2024)
The main focus of this journal is the design of a household-scale biogas digester system. The research method begins with a literature study, followed by a survey of the research location, data collection of biomass weight, analysis of biomass weightdata at the household scale, analysis of biomass weight data at the village scale, and finally drawing conclusions and providingrecommendations. The results of this thesis include, firstly, on a household scale, the maximum biomass weight obtained includescow manure weighing 47.4 kg per day and goat manure weighing 11.648 kg per day, a C/N ratio of biomass of 19.93, a volume ofwater mixed with biomass of 123,920 cm³ per day, a potential biogas energy production of 2,478,400 cm³ per day, potential electricity that can be generated is 15.118 kWh per day, material requirements for building the biogas digester system include a total need for 2,266 bricks, 619.15 kg of cement, 2.18 m³ of sand, 133.64 L of water, 0.0916 m³ of fine aggregate, 0.11 m³ of coarse aggregate, 6” PVC pipe measuring 2.9572 m, 6” PVC sockets of 2 pieces, 1/2" galvanized steel pipe measuring 0.3154 m, 1/2" galvanized sockets of 1 piece, and 1/2" gas taps with 3/8” output of 1 piece with a construction cost of Rp. 5,445,973.43, a difference in potential electricity energy compared to electricity consumption of 7.9425 kWh per day, and the implementation of a combined scheme of PLN electricity installation with a biogas generator requires additional components such as a biogas generator, a 4A Miniature Circuit Breaker (MCB), an Auto Transfer Switch (ATS), and NYY cables 2 x 1.5 mm². Secondly, on a village scale, the maximum biomass weight obtained includes cow manure weighing 679.4 kg per day and goat manure weighing 294.112 kg per day, a C/N ratio of biomass of 20.52, a volume of water mixed with biomass of 2,094,080 cm³ per day, a potential biogas energy production of 41,881,600 cm³ per day, potential electricity that can be generated is 255.48 kWh per day, the number of biogas digester systems that can be built is 16 units with a construction cost of Rp. 87,135,571.84, and the cost difference of full PLN electricity compared to a combination of PLN and biogas is Rp. 10,362,268.80 or 79%. Keywords— biomass, biogas, conversion, biogas digester system.